Oral Feeding Challenges in Children With Tracheostomy Can Improve Feeding Outcomes, Even With the Finding of Aspiration - Yi, You Gyoung; Oh, Byung-Mo; Yang, Seoyon; Shin, Hyung-Ik (Frontiers in Pediatrics, 2019)
It has been suggested that oral feeding trial has therapeutic implications for improving oral-motor and swallowing function in infants and young children fed via an enteral tube or gastrostomy. This study aimed to investigate whether oral feeding challenges in children with tracheostomy could improve feeding outcomes, even with the finding of aspiration compared to those who did not receive oral feeding at all. Children (age <7 years) with tracheostomy who had thin fluid aspiration on videofluoroscopic swallowing study (VFSS) were included in this retrospective study. Enrolled children were then divided into two feeding method groups according to the physician's decision at the time of VFSS: oral feeding (OF) group and non-oral feeding (NOF) group. Data were obtained from 47 children (median age: 49.75 months, interquartile range [IQR]: 24.08-79.42). The incidence of pneumonia within 1 year after the VFSS was not different between NOF (n=17) and OF (n=30) groups. In OF group, 11 subjects achieved full oral feeding and 16 subjects were in partial oral feeding status one year after the VFSS. On the contrary, only one subject achieved full oral feeding and 5 subjects were in partial oral feeding status in NOF group (p<0.001). Initial and follow-up penetration-aspiration scale on VFSS were different only in the OF group (p=0.003). These results suggest that oral feeding challenges might be attempted even with the findings of aspiration in infants or young children with tracheostomy.